Perbedaan Cakupan Imunisasi Polio-1 Antara Bayi Baru Lahir Yang Lahir Di Rs Dan Yang Lahir Di Rumah Bersalin Di Kota Surakarta - Wiguna, Vega Ramadhani (2016)
Background: Immunization is an effective health investment on the prevention of infectious diseases. Immunization programs implemented in Indonesia since 1956 include tuberculosis, diphtheria, pertussis, measles, polio, tetanus and hepatitis B. Appropriate guidelines PPI polio-1 immunization is given in the newborn, so it given when the baby going home or during the first visit at Hospital to avoid the transmission of vaccine virus to baby because the polio virus can be excreted through feces. Meanwhile, in maternity hospitals it given immediately after the baby is born. Purpose: Find the differences polio-1 immunization coverage among newborns born in hospital with newborns born in the maternity hospitals in the city of Surakarta. Methodology: This research was observational analytic research with cross sectional and quota sampling technique. The total sample was 384 patients. The used data analysis technique was Chi-square which was processed using Statistical Product and Service Solution (SPSS) 22.0 for Windows. Result: From the statistical calculation it was obtained that P value = 0,154 (P>0,05) that meant there was not a significant difference of polio-1 immunization coverage among newborns born in hospital with newborns born in the maternity hospitals in the city of Surakarta. Conclusion: There was not a significant difference of polio-1 immunization coverage among newborns born in hospital with newborns born in the maternity hospitals in the city of Surakarta. Keywords: polio-1 immunization, Hospitals in city of Surakarta, Maternity Hospitals in city of Surakarta